Boosting Donation Engagement: Exploring The Impact Of Accountability And Transparency On Donation Interest In Dompet Dhuafa South Jakarta - Khansa Ramadhan, Naurah; Maulidizen, Ahmad (SEAN Institute, 2024)
This research aims to investigate the impact of financial report accountability and transparency on individuals' willingness to donate to Dompet Dhuafa, located in South Jakarta. This study adopts a descriptive quantitative approach, employing multiple linear regression analysis and ensuring the validity of instruments, classical assumptions, and hypothesis testing. The study population comprises residents of South Jakarta, with a sample size of 100 respondents selected through probability sampling using simple random sampling technique. The findings of the T-test reveal significant influences, indicating that (1) accountability positively influences public interest, and (2) transparency of financial reports also positively influences public interest. Additionally, the results of the F-test demonstrate that accountability and transparency of financial reports collectively impact public interest. In conclusion, both accountability and transparency of financial reports exert partial and simultaneous effects on public interest. This suggests that higher levels of accountability and transparency in financial reporting correspond to increased public willingness to donate